ENGINEERED PAPER PLATFORM LOADED WITH GOLD NANOSPHERES TO IMPROVE SERS PERFORMANCE FOR ANALYTE DETECTION - ORZAN, F.; CAMPU, A.; SUARASAN, S.; ASTILEAN, S.; FOCSAN, M. (Studia Universitatis Babeș-Bolyai Physica, 2018)
In this paper, we report a flexible surface enhanced Raman scattering (SERS) nanoplatform based on a Whatman paper loaded with gold nanospheres via a direct immersion approach. After the fabrication and optical/morphological characterization, the SERS performance of our plasmonic nanoplatforms was tested using the non-resonant Raman p-aminothiophenol (p-ATP) analyte. Finally, the plasmonic nanoplatform developed here has demonstrated to have excellent reproducibility, the SERS efficiency being highly dependent on the AuNPs concentration loaded on the 3D flexible scaffold paper.